If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 7 = 13 + -2x Reorder the terms: 7 + x = 13 + -2x Solving 7 + x = 13 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 7 + x + 2x = 13 + -2x + 2x Combine like terms: x + 2x = 3x 7 + 3x = 13 + -2x + 2x Combine like terms: -2x + 2x = 0 7 + 3x = 13 + 0 7 + 3x = 13 Add '-7' to each side of the equation. 7 + -7 + 3x = 13 + -7 Combine like terms: 7 + -7 = 0 0 + 3x = 13 + -7 3x = 13 + -7 Combine like terms: 13 + -7 = 6 3x = 6 Divide each side by '3'. x = 2 Simplifying x = 2
| -6x-70=-11x+70 | | 9-2y-6=11 | | y=1.9x+4.5 | | 2-3+7w=8w+3 | | 0.8(x+300)=0.84x-68 | | 7a+a+6b+2b+b= | | 10k-k-7k=10 | | 14+n+6=-5 | | 7=2.5lnx+3 | | -3(4x-1)-12=-105 | | -9+8v=7v | | 6x-8=-3x-116 | | y=-2x+3y | | 3.5v+8=12.5-video | | 8d-2d+12=42 | | 75y^3+25y^2-12y-4=0 | | 9-3-7y=-8-5y | | -8x-19=54-2x | | 5v+-15v+15v+9v-11v=-18 | | 8x-3x=4x+x | | 6r+12-4=20 | | B+2.4=9.2 | | 8x-8=8(x-6) | | 11c-16=15 | | 2c+3c=15 | | 3(21+15)=3(21)+3(15) | | B=9.2 | | 14-6a=7(-8a+2) | | 0.12(y-2)+0.04y=0.20y-0.05(10) | | t-6=8-t | | -12d+11d-14-10= | | -50+2x=25+7x |